TrueDx TSH assay is an acceptable screening test for both hypo- and hyperthyroidism in the general population: correlation between trueDx TSH assay and the standard 3rd Generation TSH Chemoluminiscence Immunoassay (CMIA) - Shahar, Mohammad Arif; Omar, Ahmad Marzuki; Ab Wahab, Norasyikin; Sukor, Norlela; Kamaruddin, Nor Azmi (Korean Thyroid Association, 2017)
To determine the correlation between the TrueDx TSH assay and the standard 3rd generation chemoluminescence microparticle immunoassay (CMIA) This is a cross sectional study involving 212 healthy volunteers who participated in a hypothyroidism awareness campaigns carried out at several shopping malls in Kuala Lumpur, Malaysia. Upon obtaining an informed consent, sociodemographic characteristics and full medical history were documented, followed by a complete physical examination. Capillary blood was obtained for the TrueDx TSH assay while venous blood was withdrawn and sent to a centralized chemical pathology laboratory for TSH testing using the 3rd generation TSH CMIA (Architect system). The TSH TrueDx test machine was provided by Merck Malaysia. The mean age of the subjects was 45.2 ± 13.9 years. Majority of volunteers were females (68.4%). The ethnic distribution was 66.0% Chinese, 27.8% Malays and 5.7% Indians. The median levels for TSH measured by TrueDx assay and TSH CMIA were 1.79(1.32,2.61) and 1.08(0.70,1.48)uIU/mL respectively. The TrueDx TSH assay has a modest correlation with the 3rd generation TSH CMIA (Spearman's rho = 0.66, p < 0.001). The positive predictive value (PPV) and negative predictive value (NPV) for TrueDx assay in detecting hypothyroidism were 0.20 and 1.00 respectively, with the sensitivity and specificity of 100% and 96%. While the PPV and NPV for TrueDx assay in detecting hyperthyroidism was 0.50 and 0.98, respectively with the sensitivity and specificity of 63% and 97%. TrueDx TSH assay is too sensitive in diagnosing hypo- and hyperthyroidism on it's own (PPV 20% for hypothyroidism, PPV 50% for hyperthyroidism) but with the very high specificities and NPVs for both hypo- and hyperthyroidism it serves as a satisfactory screening test for thyroid disorders. However, subjects who returned with TSH levels suggestive of either hypo- or hyperthyroidism with TrueDx must have a confirmatory test with the 3rd generation CMIA TSH test.